2018
DOI: 10.1016/j.ehj.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of tricuspid valve endocarditis among patients presented to Ain Shams Hospital echocardiography lab; one year study

Abstract: BackgroundIsolated Tricuspid valve infective endocarditis is an infrequent diagnosis, the incidence of Tricuspid valve infective endocarditis accounts for 5% and up to 15% of IE cases.AimTo assess the prevalence and the echocardiographic characteristics of tricuspid valve endocarditis among patients presented to the echo lab of Ain Shams hospital from 1-1-2016 to 1-1-2017.MethodsThis is a retrospective study which included all patients presented to the echo lab of Ain Shams university hospital from 1st January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
1
6
1
Order By: Relevance
“…Similar findings were previously reported [30, 5, 12]. The higher incidence of IE among the young, male patients is attributed to the predominance of the injection drug users (IDUs), which is considered a problem related mainly to the young males in our Egyptian society [31]. The study revealed 75% of the IDUs were HCV positive.…”
Section: Discussionsupporting
confidence: 86%
“…Similar findings were previously reported [30, 5, 12]. The higher incidence of IE among the young, male patients is attributed to the predominance of the injection drug users (IDUs), which is considered a problem related mainly to the young males in our Egyptian society [31]. The study revealed 75% of the IDUs were HCV positive.…”
Section: Discussionsupporting
confidence: 86%
“…Further, Ludvigsen et al 24 reportedIE incidence is38-times higher for hemodialysispatients than untreated patients. Theseepidemiological changes could explain not only the increase in numbers, but also the increase in RSIE cases compared to LSIE in our IE population, especially for NODIDRSIE patients 11,14,20 . In a nutshell, patients on hemodialysis, congenital heart disease, with polymicrobial infections or malignancy have a higher mortality rate when being treated for RSIE.…”
Section: Discussionmentioning
confidence: 83%
“…Incidence of RSIE has been described as 5%-10% of IE 1 . However, recently published studies indicate an increased incidence of 10%-20% 8,11,14,20 . Our study found a similarly increased incidence of 19%.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of RSIE (90%) involve the tricuspid valve [ 8 11 ]. The rarity of right-sided congenital heart diseases and rheumatic heart diseases coupled with the low pressure/low oxygen saturation on the right chambers of the heart is believed to be the reason for the lesser frequency of RSIE as compared to the left-side infective endocarditis [ 6 , 11 ]. RSIE can be divided into three groups according to the underlying risk factors: intravenous drug users (IDUs), cardiac device carriers, and the “three noes” group (no left-sided IE, no IDUs, and no cardiac devices).…”
Section: Discussionmentioning
confidence: 99%
“…RSIE can be divided into three groups according to the underlying risk factors: intravenous drug users (IDUs), cardiac device carriers, and the “three noes” group (no left-sided IE, no IDUs, and no cardiac devices). Tricuspid valve endocarditis in nonintravenous drug users can occur in a variety of conditions including congenital heart disease, intracardiac devices, central venous catheters, and immunologically debilitated patients [ 5 , 6 , 9 ]. Intravenous drug use and the presence of cardiac devices (pacemakers, implantable automatic defibrillators, and central venous catheters) are the well-known risk factors for RSIE.…”
Section: Discussionmentioning
confidence: 99%